The role of digital readiness innovative teaching methods in music art e-learning students’ satisfaction with entrepreneur psychological capital as a mediator: Evidence from music entrepreneur training institutes - Huang, Ye (Frontiers in Psychology, 2022)
The way of our The way of our living and working has changed intensely throughout the past half-century. The era we live in is interlinked with rapid technological changes, paving the way for digitalization. The students are considered digital natives and are expected to have e-learning abilities to improve their academic effectiveness. However, digital readiness is an important factor that can play a valuable role in boosting students' e-learning abilities and satisfaction. The previous studies of students’ e-learning abilities revealed the lack of students’ digital readiness for academic achievements. Therefore, the present study aims to examine the role of digital readiness in the e-learning satisfaction of students. Based on the theory of motivation, the present study attempts to check the association of digital readiness with e-learning satisfaction. The current study also determines the relationship of digital readiness with entrepreneur psychological capital. Further, this study examines the correlation of entrepreneur psychological capital with e-learning satisfaction. The present study also assumes the mediating role entrepreneur of psychological capital and moderating role of mindfulness. For empirical analyses, this study gathered data from 376 music learning students of entrepreneur training institutes in China through a structured questionnaire method using a convenient sampling technique. This study applied partial least square structural equation modeling for empirical analyses using Smart PLS software. The present study confirmed that digital readiness positively correlates with e-learning satisfaction and psychological capital. The findings also acknowledged that psychological capital positively enhances e-learning satisfaction. The results also confirmed that psychological capital mediates the association between digital readiness and e-learning satisfaction. However, the outcomes revealed that mindfulness does not moderate the association between digital readiness and e-learning satisfaction. On the other hand, the findings acknowledged that mindfulness moderates the relationship between psychological capital and e-learning satisfaction.